Managing the Complications of Mild Therapeutic Hypothermia in the Cardiac Arrest Patient. (July 2015) - Noyes, Adam M.; Lundbye, Justin B.
Mild therapeutic hypothermia (MTH) is used to lower the core body temperature of cardiac arrest (CA) patients to 32°C from 34°C to provide improved survival and neurologic outcomes after resuscitation from in-hospital or out-of-hospital CA. Despite the improved benefits of MTH, there are potentially unforeseen complications associated during management. Although the adverse effects are transient, the clinician should be aware of the associated complications when managing the patient receiving MTH. We aim to provide the medical community comprehensive information related to the potential complications of survivors of CA receiving MTH, as it is imperative for the clinician to understand the physiologic changes that take place in the patient receiving MTH and how to prepare for them and manage them if they do occur. We hope to provide information of how to manage these potential complications through both a review of the current literature and a reflection of our own experience.